2018
DOI: 10.1021/acscombsci.8b00032
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Approach to 7-(Hetero)arylpyrazolo[1,5-a]pyrimidin-5-ones

Abstract: A modular, two-pot assembly of 7-arylpyrazolo[1,5- a]pyrimidones from aryl/heteroaryl halides and aminopyrazoles in library format was developed. Sonogashira coupling of aryl bromides with triethyl orthopropiolate, followed by in situ orthoester hydrolysis, provides access to β-aryl ynoates, which undergo regioselective cyclocondensation with aminopyrazoles. The ability to vary the C7 vector of 7-arylpyrazolo[1,5- a]pyrimidones in two steps using readily available (hetero)aryl halides significantly enhances sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Comparatively, Schmitt and co-workers established a methodology that allows the functionalization with aryl or heteroaryl groups at position 7 (compounds 39a–f ) employing substituted alkynes 38a–f ( Scheme 12 a). In addition, they took advantage of substituted pyrazoles to functionalize positions 2 and 3 (not shown) [ 50 ]. Recently, Akrami and co-workers developed a protocol capable of reduces reaction time employing dimethyl acetylenedicarboxylate ( 38g ) and the aminopyrazole 21b ( Scheme 12 b) [ 51 ].…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
“…Comparatively, Schmitt and co-workers established a methodology that allows the functionalization with aryl or heteroaryl groups at position 7 (compounds 39a–f ) employing substituted alkynes 38a–f ( Scheme 12 a). In addition, they took advantage of substituted pyrazoles to functionalize positions 2 and 3 (not shown) [ 50 ]. Recently, Akrami and co-workers developed a protocol capable of reduces reaction time employing dimethyl acetylenedicarboxylate ( 38g ) and the aminopyrazole 21b ( Scheme 12 b) [ 51 ].…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
“…Recently, Schmitt et al have reported a two-pot synthesis of 7-(hetero)aryl pyrazolo[1,5- a ]pyrimidin-5-ones from aryl (heteroaryl)halides and aminopyrazoles. 26 Nevertheless, these strategies have various drawbacks: the scope of the substrate is restricted and pyrazolo[1,5- a ]pyrimidin-5-ones were obtained in low to moderate yields.…”
Section: Introductionmentioning
confidence: 99%